Quality and maximum profit of industrial tomato as affected by distribution uniformity of drip irrigation system - Santos, Francisco Lúcio (1996)
Abstract The tomato industry reformed its system of payment by weight of tomato, introducing a corrective system based on percent level of fruit dry matter produced. Such a decision implies significant changes in the management of irrigation systems, with a need to emphasize the technological quality of the marketable product. Three levels of distribution uniformity of the irrigation system are analysed, and related production functions of crop yield and percent of dry matter are presented as well as their use on the optimisation of dry matter, expected revenues and seasonal applied water. Results are critically influenced by the distribution uniformity. They demonstrate the inter-relationship between crop production, percent fruit dry matter and irrigation management, and the importance of considering non-uniformity in the economic analysis of industrial tomato production. Decreases in uniformity lead to a reduction in dry matter production per unit land. Decreases in dry matter are also observed with increasing levels of seasonally applied water, with the optimal level always lower than the required for maximum yield. Such interaction suggests a continuous and inverse relationship between profit and water applied. However, due to the corrective system of payment, by levels of percent of dry matter produced, for some uniformity, the expected revenue follows the yield-water production function instead of the dry matter function. This fact introduces disturbances in the optimal water applied inducing higher than expected levels of water applied for profit maximisation. The simulated data also show that incentives to switch to new systems or management practices able to raise the distribution uniformity result more from profit losses than increases in water price.